Louis-Pierre Mouillard papers - Mouillard, Louis-Pierre, 1834-1897.
Correspondence, writings, notes, printed material, certificates, photographs, drawings, and other papers pertaining primarily to Mouillard's inventions. Subjects include aviation, agricultural techniques in the desert, naval technology, local politics, and bird flight and wing structure. Includes a record book of the packet boat Gabari documenting trade between Egypt, Saudi Arabia, and Tunisia. Correspondents include Octave Chanute.
French inventor and aeronautical pioneer who lived primarily in Algeria and Egypt.
Collection material in French, with English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chanute, Octave, -- 1832-1910 -- Correspondence; Gabari (Packet boat); Aeronautics; Birds; Desert reclamation; Flight; Naval research; Algeria -- Politics and government; Egypt -- Commerce; Egypt -- Politics and government; Saudi Arabia -- Commerce; Tunisia -- Commerce; Aviators; Inventors